2007
DOI: 10.1080/17517570601088539
|View full text |Cite
|
Sign up to set email alerts
|

ERP systems success: an empirical analysis of how two organizational stakeholder groups prioritize and evaluate relevant measures

Abstract: Organizations worldwide are adopting enterprise resource planning (ERP) systems. A number of studies discuss the implementation and success of such systems, but our study of the literature indicates that discussions about ERP systems success from the perspectives of key organizational stakeholders are not easy to come across. This study is designed to fill this gap in research. Using surveys in Finland and Estonia, we obtained empirical data from 66 respondents in 44 diverse, private, industrial organizations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
5

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 48 publications
0
36
0
5
Order By: Relevance
“…According to Zhang et al (2005), the ERP system quality consists of its flexibility, ease of use, reliability, short response time and useful specific functions. Ifinedo and Nahar (2007) presented the characteristics of flexibility, ease of use, ease of learning and integration to define the quality of the ERP system. Kanellou and Spathis (2011) confirmed that there is a reduction in the time and frequency of preparation of financial statements (monthly, quarterly and annual financial statements) after the adoption of an ERP.…”
Section: B Information Qualitymentioning
confidence: 99%
“…According to Zhang et al (2005), the ERP system quality consists of its flexibility, ease of use, reliability, short response time and useful specific functions. Ifinedo and Nahar (2007) presented the characteristics of flexibility, ease of use, ease of learning and integration to define the quality of the ERP system. Kanellou and Spathis (2011) confirmed that there is a reduction in the time and frequency of preparation of financial statements (monthly, quarterly and annual financial statements) after the adoption of an ERP.…”
Section: B Information Qualitymentioning
confidence: 99%
“…These changes also influence the way ERPs are developed and sold. The ERP market is prone to change, impacting not only the stakeholders in the ERP value-chain (Ifinedo and Nahar 2007;Somers and Nelson 2004), but also how these stakeholders gain competitive…”
Section: Enterprise Resource Planning Systemsmentioning
confidence: 99%
“…Secondly, researches showed that the use of external consultants is helpful for the adoption of e-business and ERP systems [ 17). So we temporally propose that Hypothesis seven: Internal-oriented culture and the tendency to proactive use of external information tend to favor HIS implementation and use.…”
Section: Shan Wang Norm Archer and Yanli Pei'mentioning
confidence: 99%